Expression optimisation of antimicrobial fusion protein variants - Wong, Long Hui. (2009)
This work reports the recombinant expression of human beta-defensin 25 fusion proteins in E. coli and various transformation experiments carried out using recombinant plasmids. HBD-25 is found to be highly expressed in the human epididymis. Like other human defensins, its ability to act as a host defense is conjectured to be in protecting human from invading or sexually transmitted microorganisms. To validate its’ antimicrobial activity in human, large amount of HBD-25 protein must be expressed in order for additional research to be conducted. As a result, the expression conditions of the HBD-25 fusion protein must be optimized to obtain high yield of HBD-25 protein per expression. The plasmid harbouring the HBD-25 gene of interest was transformed into E. coli BL21 (DE3) strain and cultured in different fermentation conditions to optimize cell expression. In part A of this report, an isopropyl β-D-1 thiogalactopyranoside concentration of 0.5mM and 5 hours of post-induction time was shown to reap the highest volumetric productivity of insoluble KSI-His-TEV-HBD25 fusion proteins (15.61g/L and 27.01g/L respectively). Part B of this report proved that TB medium and antibiotics concentration of 50mg/L gave the highest volumetric productivity of soluble TrxA-His-Enterokinase-HBD25 fusion proteins (4.70g/L and 5.27g/L respectively). Part C presented various transformations carried out using recombinant plasmids harbouring either HBD-25-TEV-fusion tags or TEV protease sequence and the factors that might affect transformation were discussed. Low plasmid concentration used for transformation was identified as the key reason for transformation failures in this report.